2000
DOI: 10.1128/jvi.74.6.2679-2686.2000
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Integrated Papillomavirus E6/E7 Promoter Is Required for Growth Suppression of Cervical Cancer Cells

Abstract: The human papillomavirus (HPV) E2 protein is an important regulator of viral E6 and E7 gene expression. E2 can repress the viral promoter for E6 and E7 expression as well as block progression of the cell cycle in cancer cells harboring the DNA of "high-risk" HPV types. Although the phenomenon of E2-mediated growth arrest of HeLa cells and other HPV-positive cancer cells has been well documented, the specific mechanism by which E2 affects cellular proliferation has not yet been elucidated. Here, we show that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
0
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 48 publications
4
127
0
4
Order By: Relevance
“…Because the papillomavirus E2 protein represses E6/E7 transcription by binding the HPV early promoter (Hwang et al, 1993(Hwang et al, , 1996Dowhanick et al, 1995;Francis et al, 2000), we analyse the effect of E2 on hWAPL expression. We observed a significant reduction of hWAPL protein levels after the infection of HPV-16 E6-and E7-expressing cervical cancer cell lines, such as CaSki and SiHa, with the retrovirus encoding E2 ( Figure 1B).…”
Section: Hpv Oncoproteins E6 and E7 Induce Hwaplmentioning
confidence: 99%
“…Because the papillomavirus E2 protein represses E6/E7 transcription by binding the HPV early promoter (Hwang et al, 1993(Hwang et al, , 1996Dowhanick et al, 1995;Francis et al, 2000), we analyse the effect of E2 on hWAPL expression. We observed a significant reduction of hWAPL protein levels after the infection of HPV-16 E6-and E7-expressing cervical cancer cell lines, such as CaSki and SiHa, with the retrovirus encoding E2 ( Figure 1B).…”
Section: Hpv Oncoproteins E6 and E7 Induce Hwaplmentioning
confidence: 99%
“…Introduction of an ectopic E2 gene into a number of cervical carcinoma cells lines results in a great reduction in E6͞E7 mRNA and in substantial growth inhibition (32-36, 38, 42). E2-mediated growth inhibition is observed only in cells containing HPV DNA, and E2-induced reduction in HeLa cell colony formation is prevented by constitutive expression of the HPV16 E6 and E7 genes (32,38,41,42), indicting that repression of E6͞E7 is required for the growth inhibitory effect. …”
mentioning
confidence: 99%
“…Repression of viral oncoproteins expression would hence restore growth control in these cells by targeting E6 and E7. For this purpose, several approaches have been used such as antisense strategies (Steele et al, 1993;He et al, 1997), delivering HPV E2 gene to directly repress E6 and E7 transcription (Hwang et al, 1996;Francis et al, 2000), targeting E6 oncoprotein by peptide aptamers (Butz et al, 2000) and inhibiting E6/E7 transcription by nuclear export inhibitors (Hietanen et al, 2000). Although these strategies demonstrated that down-regulating E6/E7 could restore growth control, their ecacy was limited due to insucient gene delivery into tumors or to cytotoxic eects induced in normal cells.…”
Section: Introductionmentioning
confidence: 99%